A National Portrait of Domestic Violence Courts (2009) - Melissa Labriola, Sarah Bradley, Chris O’Sullivan, Michael Rempel and Samantha Moore (My University, 2016)
In providing a comprehensive national profile of domestic violence courts (DVCs), this study explored how criminal DVCs have evolved, their rationale, and how their operations vary across the United States. (palabras claves: violencia intrafamiliar, tribunales VIF)